Pellets of proof: First glimpse of the dietary composition of adult odonates as revealed by metabarcoding of feces - Kaunisto KM; Roslin T; Saaksjarvi IE; Vesterinen EJ (WILEY, 2022)
Recent advances in molecular techniques allow us to resolve the diet of unstudied taxa. Odonates are potentially important top-down regulators of many insects. Yet, to date, our knowledge of odonate prey use is based mainly on limited observations of odonates catching or eating their prey. In this study, we examine the potential use of metabarcoding in establishing the diet of three adult odonate species (Lestes sponsa, Enallagma cyathigerum, and Sympetrum danae) at a site in southwestern Finland. To this purpose, we compared three different methods for extracting DNA from fecal samples: the Macherey-Nagel Nucleospin XS kit, a traditional salt extraction, and the Zymo Research Fecal Microprep kit. From these extracts, we amplified group-specific mitochondrial markers (COI and 16S rRNA) from altogether 72 odonate individuals, and compared them to comprehensive reference libraries. The three odonate species show major overlap in diet, with no significant differences between individuals of different size and/or gender, reflecting opportunistic foraging of adult odonates. Of a total of 41 different prey species detected, the most frequently consumed ones were Diptera, with additional records of six other orders. Based on our data, the best DNA extraction method is the traditional salt extraction, as it provides the most information on prey content while also being the most economical. To our knowledge, this is the first study to resolve the species-level diet of adult odonates. Armed with the appropriate methodological caveats, we are ready to examine the ecological role of odonates in both terrestrial and aquatic food webs, and in transferring subsidies between these two realms.